Are early antero-posterior and lateral radiographs predictive of clubfoot relapse requiring surgical intervention in children treated by Ponseti method?. (February 2022) - Li, Jingchun; Xu, Chenchen; Li, Yiqiang; Liu, Yuanzhong; Xu, Hongwen; Canavese, Federico
Purpose: To investigate the value of antero-posterior and lateral radiographs in predicting clubfoot relapse after treatment with the Ponseti method. Methods: This was a retrospective review of 104 children (157 feet) younger than 3 months of age with idiopathic clubfoot treated using the Ponseti method at our institution between January 2007 and December 2014. All patients underwent Achilles tenotomy and were divided into two groups according to the need for further surgery to correct the deformity: relapsed group (24 patients; 36 feet) and non-relapsed group (80 patients; 121 feet). All antero-posterior and lateral foot radiographs were performed less than 3 months after Achilles tenotomy. The talo-calcaneal (TC-AP) and talus-first metatarsal (TM-AP) angles were measured in the antero-posterior view, while the tibio-calcaneal (TIC-L), talus-first metatarsal (TM-L), and talo-calcaneal (TC-L) angles were measured in the lateral view. The multi-factor logistic regression model of the stepwise selection method was used to predict the relapse of clubfoot deformity from the potential predictive values. Results: The mean age at initial plain radiography examination was 99.45 ± 21.54 days. Differences in TC-AP, TM-AP, TC-L, and TIC-L between the two groups were statistically significant. However, only TM-AP and TIC-L were included in the " risk of relapse " formula using the multi-factor logistic stepwise selection method. Conclusion: Early antero-posterior and lateral radiographs in children younger than 3 months of age at initial Ponseti treatment have positive predictive value for relapse. Reduced TM-AP angle and increased TIC-L were associated with an increased risk of relapse. Level of evidence: level III.